Transformasi Ibadah: Khatmil Qur’an Online di Kalangan Muslimat NU Lampung Timur - Fikry Mahfudz Ikhsanudin; Eka Prasetiawati (Journal of Islamic Scriptures in Non-Arabic Societies, 2024)
This research examines the transformation of worship practices in the digital era, especially in the context of Khatmil Qur'an Online among Muslimat NU Lampung Timur. By applying the concept of Living Qur'an Studies, this research reveals how online Qur'anic Khatmil meetings affect religious experience and social transformation in society. The results highlight that Khatmil Qur'an is not only a religious ritual but also an integral part of religious education, student motivation, and a driver of social integration in rural communities. Using Talal Asad's discursive approach, the analysis shows significant differences between online and offline Khatmil Qur'an practices, with the impact of technology and digital spaces accelerating changes in religious discursive traditions. The research provides a holistic insight into this phenomenon through qualitative research methods involving in-depth interviews and participatory observation studies. The practice of Khatmil Qur'an Online is not just a ritual but also part of an evolving process of religious meaning construction in a non-Arabic society. The success of this practice in embracing technology as a means of worship shows that digital religion is not simply the replacement of traditional ways but rather the integration of technology as an integral part of the religious way of life in the digital era.